Integrating Geography Education and Sustainable Tourism: A SWOT-Based Approach at Galesong Beach, Indonesia - Syamsunardi; Syarif, Erman; Nyompa, Sukri; Kajornsin, Boonreang; Ikhwana, Nur (CV Bumi Spasial, 2024)
Enhancing the quality of education can be achieved by incorporating This study aims to be able to find out the potential contained in galesong beach beach tourism objects and the strategy of developing galesong beach attractions in Tamalate Village, North Galesong District, Takalar Regency. This type of research is mixed methods research, meaning research that can produce descriptive and statistical data both in written and oral form. The subjects of the study, the owners and managers of galesong beach tourism, the local community and the visitors. The data analysis involves SWOT analysis, which is used to assess both the internal strengths and weaknesses and the external opportunities and threats related to the development of Galesong Beach as a tourist destination. Data analysis techniques use SWOT analysis. The results indicate that Galesong Beach has a ‘worth visiting’ rating, with an evaluation score of 76.25%. This high score is attributed to the supporting elements of the destination, such as adequate accommodation, accessibility, facilities, and infrastructure, all of which enhance its attractiveness to tourists. The SWOT analysis places the Galesong Beach development strategy in Quadrant I, suggesting a Rapid Growth Strategy. This positioning indicates that Galesong Beach should focus on strategies to accelerate visitor growth, leveraging its strengths to capitalize on opportunities for rapid expansion. That is, Galesong Beach attractions are in a strategy to increase the growth rate of tourist visitors by using faster time.